Fredric Wertham papers - Wertham, Fredric, 1895-1981.; Wertham, Fredric, 1895-1981.
Correspondence, memoranda, writings, speeches and lectures, reports, research notes, patient case files, psychiatric tests, transcripts of court proceedings, biographical information, newspaper clippings, drawings, photographs, and other materials pertaining primarily to Wertham's career in psychiatry.
Topics include abused children, censorship, civil rights, the physiological effect of drugs, freedom of speech, juvenile delinquency, pornography, race relations and racism, sex crimes, violence, violence in comic books, mass media, motion pictures, and television, and violent crime. Includes materials relating to Wertham's testimony as an expert witness in desegregation cases; his work in New York, N.Y., with the Lafargue Clinic, a psychiatric clinic for African Americans, and the Quaker Emergency Service Readjustment Center for sexually maladjusted individuals; and his art collection particularly paintings by El Lissitzky. Also includes notes, drafts, and related materials for Wertham's major works including Seduction of the Innocent (1954); a patient case file, correspondence, and writings by or about Wertham's patient, psychoanalyst Horace Westlake Frink, and correspondence between Frink and Sigmund Freud; and correspondence, writings, and other papers relating to Wertham's mentors, Emil Kraepelin and Adolf Meyer, and to his Lafargue associate, Hilde Mosse. Correspondents include Taylor Caldwell, Emil Arthur Gutheil, Langston Hughes, Ernest Jones, Alfred C. Kinsey, Ida Macalpine, Thomas Mann, Arthur Miller, Ella Winter, and Richard Wright.
Psychiatrist. Original spelling of name: Friedrich Ignatz Wertheimer.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Caldwell, Taylor, -- 1900-1985 -- Correspondence; Freud, Sigmund, -- 1856-1939 -- Correspondence; Frink, Horace Westlake, -- 1883-1936 -- Correspondence; Gutheil, Emil Arthur, -- 1899-1959 -- Correspondence; Hughes, Langston, -- 1902-1967 -- Correspondence; Jones, Ernest, -- 1879-1958 -- Correspondence; Kinsey, Alfred C. -- 1894-1956 -- Correspondence; Kraepelin, Emil, -- 1856-1926.; Lissitzky, El, -- 1890-1941.; Macalpine, Ida -- Correspondence; Mann, Thomas, -- 1875-1955 -- Correspondence; Meyer, Adolf, -- 1866-1950.; Miller, Arthur, -- 1915-2005 -- Correspondence; Mosse, Hilde L; Winter, Ella -- Correspondence; Wright, Richard, -- 1908-1960 -- Correspondence; Lafargue Clinic (New York, N.Y.); Quaker Emergency Service Readjustment Center (New York, N.Y.); Abused children; African Americans -- Psychology; African Americans -- Segregation; Art -- Collectors and collecting; Censorship; Civil rights; Comic books, strips, etc. -- Psychological aspects; Drugs -- Physiological effect; Freedom of speech; Juvenile delinquency; Pornography; Psychiatric clinics -- New York (State) -- New York; Race relations; Racism; Sex (Psychology); Sex crimes; Violence -- Social aspects; Violence in mass media; Violence in motion pictures; Violence on television; Violent crimes; Psychiatrists